Perceptions on psychiatric nursing care at a general hospital inpatient unit - Renata Marques de Oliveira; Antonio Carlos Siqueira Júnior; Antonia Regina Ferreira Furegato (Acta Scientiarum. Health Sciences, 2016)
The objective was to investigate the perception of nurses, nursing assistants and patients about nursing care at a general hospital psychiatric unit. Exploratory study with 16/20 nursing professionals and 27/84 patients from the psychiatric inpatient unit of a general hospital. Interviews were based on guiding questions about the nursing care in said unit. Thematic content analysis was adopted. The subjects acknowledge that nursing promotes the recovery of patients, that it is essential during hospitalization, and defend that working in psychiatry requires a taste and profile for it. The patients value warmth, attention, serenity, good mood, patience, concern, presence, promptness, respect and responsibility. The professionals value affection, dedication, effort, patience, security and serenity. Professionals and patients wonder if changes in nursing care during hospitalization stimulate independence/autonomy for discharge or reflect carelessness. In conclusion, nursing care is essential during psychiatric hospitalization, but it requires that professionals like it and have the right profile.